EFEKTIVITAS MEDIA WORDWALL DALAM MENINGKATKAN KEMAMPUAN KOSA KATA SISWA KELAS V SDN 2 CIKAJANG - Ayu Puji Rahayu; Sumiati Agphyra S.; Neneng Hartini; Dini Windarini (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Vocabulary is a fundamental component in mastering the Indonesian language, serving as the basis for comprehension and effective communication. However, elementary students’ vocabulary proficiency remains relatively low, which affects their ability to understand and convey information accurately. This study aims to examine the effectiveness of the Wordwall digital learning media in improving vocabulary mastery among fifth-grade students at SDN 2 Cikajang. The research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 25 students. Instruments used include vocabulary tests and statistical analyses such as normality test, homogeneity test, paired sample t-test, and simple regression analysis. The results revealed a significant improvement in students’ vocabulary achievement. The average score increased from 26.72 (pretest) to 88.16 (posttest). The paired sample t-test showed a significance value of 0.000 (< 0.05), indicating a statistically significant difference before and after the treatment. However, the regression analysis revealed that learning motivation did not have a significant effect on learning outcomes (sig. = 0.700 > 0.05). The findings suggest that Wordwall is effective in enhancing vocabulary acquisition, regardless of students' motivation levels. This indicates that interactive and engaging digital media can independently support students' learning outcomes and should be considered as an innovative alternative in vocabulary instruction. Keywords: Wordwall, vocabulary, learning media, learning outcomes, learning motivation